2012
DOI: 10.1111/j.1439-0272.2012.01297.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abamectin exposure on semen parameters indicative of reduced sperm maturity: a study on farmworkers in Antalya (Turkey)

Abstract: Environmental exposure to pesticides may cause serious health risks including fertility and reproductive function. The aim of this study was to highlight whether there is a relationship between exposure to abamectin and male fertility parameters of farmworkers. Twenty male farmworkers who were using abamectin and 20 men not exposed to pesticides were recruited as experimental and control groups, respectively. Semen analysis, molecular markers of sperm maturity and serum reproductive hormone levels were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…These avermectins are fermentation products of the soil bacterium Streptomyces avermitilis and have been used as acaricides and nematicides (Burg et al, 1979). In this one study, men exposed to the pesticide had significantly lower sperm motility and higher semen volume compared to unexposed controls (Celik-Ozenci et al, 2012). Animal models have shown abamectin to be deleterious to sperm count and motility (Celik-Ozenci et al, 2011) and to reduce fertility in rats (Elbetieha and Da’as, 2003).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…These avermectins are fermentation products of the soil bacterium Streptomyces avermitilis and have been used as acaricides and nematicides (Burg et al, 1979). In this one study, men exposed to the pesticide had significantly lower sperm motility and higher semen volume compared to unexposed controls (Celik-Ozenci et al, 2012). Animal models have shown abamectin to be deleterious to sperm count and motility (Celik-Ozenci et al, 2011) and to reduce fertility in rats (Elbetieha and Da’as, 2003).…”
Section: Discussionmentioning
confidence: 74%
“…Organophosphates (OP) were shown to be associated with lowered sperm parameters in six of the studies (Hossain et al, 2010; Perez-Herrera et al, 2008; Perry et al, 2007, 2011; Recio-Vega et al, 2008; Yucra et al, 2008). One study found an association between the pesticide abamectin and decreased sperm motility (Celik-Ozenci et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It catalyses the phosphorylation of creatine to form creatine phosphate and vice versa. Such chemical shuttle leads to generation of adenosine triphosphate that is required to drive the biochemical processes in the spermatozoa (Celik‐Ozenci et al, 2012). Therefore, the proper creatine kinase activity should be very crucial for adequate sperm function, particularly sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular priority for consideration should be the large variation found in sensitivity among different species and life stages (noted above) and whether a sufficient diversity of species has been tested to characterise the general toxicity of abamectin in the marine environment. In addition, environmentally relevant exposure times should be considered; for example, longer-term chronic exposure of adults to abamectin may be relevant if this substance accumulates in benthic sediments, potentially resulting in sub-lethal effects that modify reproductive stages (as observed in terrestrial studies Elbetieha & Da'as 2003, Celik-Ozenci et al 2011, Celik-Ozenci et al 2012. When combined with the understanding gained from future studies addressing these issues, our findings might then better inform decision-making regarding the use of abamectin in marine antifouling products, enabling the prevention of biofouling while also limiting unintended impacts in the marine environment.…”
Section: Discussionmentioning
confidence: 99%